2017
DOI: 10.1021/acscatal.7b00844
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory (DFT) Study To Unravel the Catalytic Properties of M-Exchanged MFI, (M = Be, Co, Cu, Mg, Mn, Zn) for the Conversion of Methane and Carbon Dioxide to Acetic Acid

Abstract: The conversion of greenhouse gases, such as CO2 and CH4, to value chemicals is a major challenge, because of the high stability of both molecules. In this study, density functional theory (DFT) calculations with long-range corrections and ONIOM were used to analyze the reaction mechanism for the conversion of CO2 and CH4 to acetic acid with MFI zeolite exchanged with Be, Co, Cu, Mg, Mn, and Zn cations. Our results demonstrate that (a) the highest reaction barrier on the reaction mechanism is CH4 dissociation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
65
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 60 publications
6
65
1
3
Order By: Relevance
“…This finding further support the proposal that the radical oxygen is a key factor determining the catalytic activity of the active site for C−H bond activation ,, , . Calculations on a broad range of metal‐exchanged zeolites by Curet‐Arana and co‐workers showed that the barrier for C−H bond cleavage is directly related to the energy of the lowest unoccupied molecular orbital (LUMO) and the electronegativity of active site in the metal exchanged zeolites . A periodic hybrid DFT study by Solans‐Monfort et al on the interaction of model adsorbents with Cu and Fe‐exchanged zeolites highlighted the importance of the local environment of EF sites for their adsorption properties and reactivity …”
Section: Lewis Acidity Of Zeolitesmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding further support the proposal that the radical oxygen is a key factor determining the catalytic activity of the active site for C−H bond activation ,, , . Calculations on a broad range of metal‐exchanged zeolites by Curet‐Arana and co‐workers showed that the barrier for C−H bond cleavage is directly related to the energy of the lowest unoccupied molecular orbital (LUMO) and the electronegativity of active site in the metal exchanged zeolites . A periodic hybrid DFT study by Solans‐Monfort et al on the interaction of model adsorbents with Cu and Fe‐exchanged zeolites highlighted the importance of the local environment of EF sites for their adsorption properties and reactivity …”
Section: Lewis Acidity Of Zeolitesmentioning
confidence: 99%
“…[108,116b, 117, 125] Calculations on a broad range of metal-exchanged zeolites by Curet-Arana and co-workers showed that the barrier for CÀ H bond cleavage is directly related to the energy of the lowest unoccupied molecular orbital (LUMO) and the electronegativity of active site in the metal exchanged zeolites. [126] A periodic hybrid DFT study by Solans-Monfort et al on the interaction of model adsorbents with Cu and Fe-exchanged zeolites highlighted the importance of the local environment of EF sites for their adsorption properties and reactivity. [127] Nørskov and co-workers have computationally screened the activity of wide variety of oxide-and zeolite-based catalysts for the activation of CÀ H bonds in methane.…”
Section: Structure-reactivity Relationshipsmentioning
confidence: 99%
“…Unfortunately, the reaction is thermodynamically unfavorable under moderate conditions ( G 298K = 71.2 kJ/mol). Many works are devoted to selectively break the C-H bond in CH 4 and simultaneously utilize the inertness of CO 2 to realize C-C coupling for the synthesis of high-value chemicals [3][4][5][6][7]. Most of these works are based on theoretical calculation and experiments which always require additional energy supply (such as plasma), few in-situ characterizations studies have been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Sustituciones de la zeolita MFI con otros metales como cobre (Cu) y hierro (Fe) también se han estudiado para la activación de CH4 [5]- [7]. La sustitución de Cu se puede dar de dos maneras: Mediante la formación de "oxoclusters" [Cu-O-Cu] 2+ o mediante la sustitución sencilla de Cu +2 en los anillos de MFI (Cu-MFI) [8], [9]. La barrera energética obtenida para la disociación de metano en [Cu-O-Cu] 2+ (82 kJ/mol) es menor que la obtenida en Cu-MFI (129 kJ/mol).…”
Section: Introduccionunclassified